Natural killer cells in experimental and human leishmaniasis - Bogdan, Christian (Frontiers in Cellular and Infection Microbiology, 2012)
Infections with parasites of the genus Leishmania lead to a rapid, but transient activation of natural killer (NK) cells. In mice activation of NK cells requires a toll-like-receptor 9-dependent stimulation of dendritic cells followed by the production of IL-12. Although NK cells appear to be non-essential for the ultimate control of cutaneous and visceral leishmaniasis and can exhibit immunosuppressive functions, they form an important source of interferon (IFN)-gamma, which elicits antileishmanial activity in macrophages and helps to pave a protective T helper cell response. In contrast, the cytotoxic activity of NK cells is dispensable because Leishmania-infected myeloid cells are largely resistant to NK-mediated lysis. In human cutaneous and visceral leishmaniasis the functional importance of NK cells is suggested by reports demonstrating (a) a direct activation or inhibition of NK cells by Leishmania promastigotes, (b) the suppression of NK cell numbers or activity during chronic, non-healing infections and (c) by the recovery of NK cell activity following treatment. This review aims to provide an integrated view on the migration, activation, inhibition, function and therapeutic modulation of NK cells in experimental and human leishmaniasis.